Precificação de ativos sem cotação corrente de mercado na indústria de private equity e venture capital no Brasil - Guilherme, Ronie Vinícius (2015)
This paper studies the private equity and venture capital market in Brazil, particularly with regard to the valuation methodologies, in order to identify the method that best fits the Brazilian reality to measure assets without quotation in current market. Will be discussed the major foreign markets, namely the United States and Europe, as well as specific characteristics of this market in Brazil and presented how the Brazilian authorities deal with this theme, since the assets covered here have no marking to market , as in other funds disciplined by this authority. Then will be described the methodologies and investigated the ways in which organizations approach the management methods in their rules. Finally, to achieve the main purpose, will be identified the behavior of the value of shares in the lifetime of the funds as an indicator of the most appropriate method.